Exploration of the relationship between gastric cancer and nutritional risk factors: insights from the Korea National Health Insurance Database - Kim, You Na; Kim, Chi Young (Frontiers in Nutrition, 2025)
Background/ObjectivesGastric cancer is the third most common cause of cancer-related deaths. Gastric cancer rates vary across regions, which may be attributable to factors such as Helicobacter pylori infection, environmental factors, and genetic predispositions. We examined the association between gastric cancer, nutrient intake, and lifestyle parameters in Korean adults.MethodsThis study utilized the KNHANES dataset (2012–2016) to explore the nutritional risk factors associated with gastric cancer. Multivariable analysis was conducted to confirm the association between micronutrients and specific food items using questionnaires designed to collect data on individuals’ consumption frequency and nutrient intake.ResultsThis study enrolled 18,894 participants, including 229 diagnosed with gastric cancer. Factors associated with gastric cancer included male sex, older age, low body-mass index, and frequent consumption of food outside the home. Multivariate analysis indicated that a lower intake of protein (odds ratio [OR] 0.98, 95% confidence interval [CI] 0.97–0.99, p < 0.001), fat (OR 0.99, 95% CI 0.98–0.99, p < 0.004), and thiamine (OR 0.59, 95% CI 0.45–0.76, p < 0.001) and a higher intake of niacin (OR 1.05, 95% CI 1.02–1.08, p < 0.001) were correlated with an increased risk of gastric cancer. Additionally, specific dietary items, such as tteok (rice cake) and soju, contributed to an elevated gastric cancer risk (OR 1.21, 95% CI, 1.01–1.40; OR 1.14, 95% CI, 1.03–1.25; p < 0.001).ConclusionWe found an association between gastric cancer and various nutritional and lifestyle parameters. Nutrient intake and lifestyle-related factors significantly influence the prevalence of gastric cancer, suggesting that tailored interventions could mitigate this risk in specific populations.